Desain Perpustakaan Generasi Z dan Alpha (antara Regulasi, Pendanaan, dan Teknologi) - Nurdiansyah Nurdiansyah (Jurnal Pustaka Ilmiah, 2022)
Information technology is now unstoppable, this is the impact of the continued development ofscience. To support this, the library must also be designed to follow the progress of the times, this is done to support the need for digital information. The formulation of the problem raised focuses on regulatory, funding, and technology aspects in creating a technology-based librarywhich is the main concern so that it can be seen in terms of what needs to be improved in the future so that the library that is run will continue to develop according to the needs of generations Z and Alpha. This research uses the literature study method by looking at Law No.43 of 2007 concerning Libraries as a basis. The results obtained from this research are that libraries in generation Z and Alpha need to be designed in such a way according to the regulations in law no. 43 of 2007.